2013
DOI: 10.3748/wjg.v19.i45.8247
|View full text |Cite
|
Sign up to set email alerts
|

Novel therapies for constipation

Abstract: Constipation is a common medical problem and when standard laxatives fail it can be difficult to treat. Different aetiologies require tailored therapeutic approaches. Simple constipation may only require dietary manipulation while severe neurological or slow transit constipation may need pharmacologic intervention. Recently new drug therapies have been introduced. PubMed and Ovid were searched for reviews, systematic reviews and meta-analysis published since 2003 using the terms: constipation, prucalopride, li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 25 publications
0
17
0
1
Order By: Relevance
“…55,56 In vitro studies have clearly demonstrated that MC activation alters intestinal epithelial ion transport directly or indirectly (via intrinsic or extrinsic nerves), 57,58 through recording the transepithelial short-circuit current of the intestinal mucosal tissues or epithelial cell monolayers. In sensitized mast cell-deficient mice, secretory response to serosal antigen was reduced by 70% in comparison to normal congenic mice, but fully restored after reconstitution of intestinal mast cell population by injecting bone marrow-derived mast cell precursors.…”
Section: Mast Cells Regulate Epithelial Secretionmentioning
confidence: 99%
“…55,56 In vitro studies have clearly demonstrated that MC activation alters intestinal epithelial ion transport directly or indirectly (via intrinsic or extrinsic nerves), 57,58 through recording the transepithelial short-circuit current of the intestinal mucosal tissues or epithelial cell monolayers. In sensitized mast cell-deficient mice, secretory response to serosal antigen was reduced by 70% in comparison to normal congenic mice, but fully restored after reconstitution of intestinal mast cell population by injecting bone marrow-derived mast cell precursors.…”
Section: Mast Cells Regulate Epithelial Secretionmentioning
confidence: 99%
“…While pharmacological therapies, such as prucalopride, linaclotide, and lubiprostone, are effective and relatively safe for the IBS-constipation variant [9], in general, diet and food choice are initially considered for patients with IBS in order to improve their gut symptoms [10].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these limitations, novel pharmacological agents against constipation have been developed recently, such as 5-hydroxytryptamine type 4 receptor (5-HT 4 ) agonists, type 2 chloride channel agonists, and guanylate cyclase C agonists. [7][8][9][10] In particular, prucalopride (a selective 5-HT 4 agonist) stimulates intestinal motility effectively, has a good safety profile, and is well tolerated for treatment of severe functional constipation. [11][12][13] DA-9701 (Motilitone), a newly developed prokinetic agent for treating patients with functional dyspepsia, is approved for this purpose in South Korea.…”
Section: Introductionmentioning
confidence: 99%